EFFECTIVENESS OF PROMOTION MIX-BASED MARKETING COMMUNICATION IN INCREASING CONSUMER PERCEPTION (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Marketing communication has become an essential strategy for improving customer engagement and maintaining competitiveness in the automotive service industry. This study aims to evaluate the effectiveness of marketing communication implemented by Planet Ban Pademangan Branch, North Jakarta, from the perspective of consumers. A quantitative descriptive research design was employed using a saturated sampling technique involving 37 customers. Primary data were collected through structured questionnaires using a five-point Likert scale, while supporting data were obtained from company documents and relevant literature. The study assessed four dimensions of the promotion mix, namely direct marketing, sales promotion, advertising, and personal selling. Data were analyzed through tabulation and the calculation of the average score for each indicator using the Stanford Labovitz method. The findings reveal that the overall effectiveness of marketing communication achieved an average score of 3.99, indicating a Good level of effectiveness. Among the four dimensions, sales promotion recorded the highest performance, with attractive tire purchase promotions obtaining the highest score (4.22), followed by personal selling. Conversely, telephone-based customer service communication received the lowest score (3.59), suggesting the need for service quality improvement. Overall, the integration of promotion mix strategies has effectively supported customer communication and strengthened positive consumer perceptions. The study recommends enhancing telephone communication quality and optimizing digital marketing channels, particularly WhatsApp and Instagram, to improve customer experience, strengthen long-term relationships, and increase marketing communication effectiveness.